A study on job satisfaction of higher secondary school teachers in Madurai. Issue 5 (4th July 2022) - Vinodhini, R.; Ramkumar, S.
Abstract: Job satisfaction means feelings about one's job that can only be inferred from the employee but not seen on naked eye. It is bunch of positive and ominous sentiments, with which employees view their work. It is how much joy or satisfaction related with a task an employee gets on performing his job. On the off chance that employee like his occupation seriously he will encounter high work fulfillment. In the event that he disdain his occupation, he will encounter job dissatisfaction. Job satisfaction is the ultimate feeling of a human after completing a job. The job satisfaction can be obtained to the extent the job fulfills the needs and wants of the person's consistency with the expectations and values. When all the expectations are met, the impact reflects in the performance. Employees who are not satisfied in their occupations frequently tempt to resign than those who are satisfied. The general idea is that happy people are more productive than unhappy people.